Influence of combined heat treatment and densification on mechanical properties of poplar wood - Düzkale Sözbir, Gonca; Bektaş, İbrahim; Kılıç Ak, Ayşenur (Maderas. Ciencia y Tecnología, 2019)
In this study, influence of combined heat treatment and densification on mechanical properties of poplar wood (Populus usbekistanica) such as density, EMC, compression strength, modulus of elasticy, modulus of rupture and static bending strength were investigated. Poplar samples were subjected to a temperature of 120oC, 160oC and 200oC for 1 and 3h. After the heat treatment, the heat treated samples were compressed in a hot press at a temperature of 120oC, press pressure of 50 bar and press time of 30 minutes for densification. The results showed that the heat treatment affected the densification with increasing density. Additionally, the heat treatment decreased modulus of rupture (MOR), modulus of elasticity (MOE) and impact bending strength (IBS) with increasing temperature for undensified poplar wood. In conclusion, densification process has improved all the mechanical tested properties.